Mikhail Bakhtin and Walter Benjamin - Beasley-Murray, T. author. aut Link
IX, 223 p.
Keywords: This first comparative study of the philosophers and literary critics, Walter Benjamin and Mikhail Bakhtin, focuses on the two thinkers' conceptions of experience and form, investigating parallels between Bakhtin's theories of responsibility, dialogue, and the novel, and Benjamin's theories of translation, montage, allegory, and the aura.